High‐Throughput Aging System for Parallel Maximum Power Point Tracking of Perovskite Solar Cells. Issue 6 (4th April 2022) - Köbler, Hans; Neubert, Sebastian; Jankovec, Marko; Glažar, Boštjan; Haase, Martin; Hilbert, Clemens; Topič, Marko; Rech, Bernd; Abate, Antonio
Abstract : In this research instrument article, the capabilities and details of a high‐throughput aging system for parallel maximum power point tracking (MPPT) of perovskite solar cells (PSCs), capable of assessing the operational stability of a large number of devices, are presented. The intention is to provide insights into the machine and the development process to engineers who want to create a similar system and eventually make MPPT stability testing of PSCs a standard procedure. Abstract : Stability is one of the remaining challenges to be solved for perovskite solar cells (PSCs) to become commercialised. Especially, the operational stability under maximum power point tracking (MPP‐tracking) is highly relevant to emulate realistic working conditions. This article describes a high‐throughput aging system that can MPP‐track >350 solar cells in parallel under controlled conditions, including atmosphere, temperature, and illumination.